Hubungan Panjang-Berat dan Reproduksi Ikan Kuniran Upeneus sulphureus (Cuvier, 1829) di PPI Kalianda, Lampung Selatan - M Aldhy Nur Pradana; Indra Gumay Yudha; Abdullah Aman Damai; Suparmono Suparmono (Journal of Aquatropica Asia, 2022)
Sulphur goatfish (Upeneus sulphureus) is the dominant caught with a fairly high level of utilization. This research aimed to analyze aspects of growth and reproduction sulphur goatfish caught by rampus nets landed at the fishing port of PPI Kalianda. Growth aspects that were observed included the length-weight, while the reproductive aspects observed is the sex ratio, gonad maturity level, and the size of sulphur goatfish at first maturity. This research was conducted in May-July 202 with the research method used simple random sampling method. The fish samples obtained during the study were 600 individuals, the results showed that Sulphur goatfish had negative allometric growth. The equation for the long-weight relationship of sulphur goatfish is log W = -4,6 + 2,9 log L or W = 2,8x10-5L2,9. The sex ratio of sulphur goatfish in May and July were not 1: 1, while the ideal condition was achieved in June. The gonad maturity level distribution of sulphur goatfish was dominated by TKG III and IV for female, while male sulphur goatfish was dominated by TKG II and III. Size at first maturity of sulphur goatfish females was 169,1 ± 1,03mm.